The influence of design and everyday practices on individual heating and cooling behaviour in residential homes - Eon, Christine; Morrison, Greg; Byrne, Joshua (2017)
Emerging results from practice-based research demonstrate that energy efficient houses often do not meet theoretical energy use based on the current standards of residential buildings. A factor influencing this inconsistency is related to user behaviour and everyday practices. The objective of this research is to uncover some of the complexities associated with the practices of heating and cooling in the home, which are influenced by motivations, knowledge and technologies, including the use of photovoltaic panels. For this purpose, ten Australian houses were established as embedded Living Labs and monitored for over a year. The results confirm the variation of energy use in houses; in this case, similar designs vary by up to 33%. The type of heating and cooling systems that houses rely on through the year was found to be a major determinant in energy use. However, energy variation between houses is also linked to intra-home practices and behaviours. This research found that individuals living in the same house may have different motivations and/or heating and cooling practices, affecting the overall energy use. For instance, one individual who is motivated to save on energy bills might turn on appliances during the day to make the most of solar panels or use the heater for brief periods of time, whilst another inhabitant of the same house might turn on the heater for extended periods out of habit or to achieve a hedonic experience. The adoption of an explanatory design mixed-method approach to study everyday practices in the home showed that the routines, household configuration, technology and varied occupant motivations impact on the practice of ambient heating and cooling, impacting its regularity, duration, time of the day and intensity.